2022
DOI: 10.1002/inf2.12272
|View full text |Cite
|
Sign up to set email alerts
|

A review of hard carbon anode: Rational design and advanced characterization in potassium ion batteries

Abstract: K‐ion batteries (KIBs) have attracted tremendous attention and seen significant development because of their low price, high operating voltage, and properties similar to those of Li‐ion batteries. In the field of development of full batteries, exploring high‐performing and low‐cost anode materials for K‐ion storage is a crucial challenge. Owing to their excellent cost effectiveness, abundant precursors, and environmental benignancy, hard carbons (HCs) are considered promising anode materials for KIBs. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 135 publications
(148 reference statements)
2
60
0
Order By: Relevance
“…
With the booming of renewable energy sources and the extensive promotion of large-scale energy storage devices, sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) exhibit the potential to share the pressure on expensive lithium-ion batteries (LIBs) in energy storage field. [1][2][3][4][5] The fascinating advantages of SIBs and PIBs include abundance of sodium and potassium resources, cost effectiveness, superior safety properties, and similar operating mechanism with LIBs. [6][7][8][9][10][11][12] However, the commercial graphite anode exhibits a low theoretical capacity, largely limiting its practical application.
…”
mentioning
confidence: 99%
“…
With the booming of renewable energy sources and the extensive promotion of large-scale energy storage devices, sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) exhibit the potential to share the pressure on expensive lithium-ion batteries (LIBs) in energy storage field. [1][2][3][4][5] The fascinating advantages of SIBs and PIBs include abundance of sodium and potassium resources, cost effectiveness, superior safety properties, and similar operating mechanism with LIBs. [6][7][8][9][10][11][12] However, the commercial graphite anode exhibits a low theoretical capacity, largely limiting its practical application.
…”
mentioning
confidence: 99%
“…[40,41] For PIBs, the reaction mechanisms and different carbon anodes with their design strategies of heteroatoms doping, structure engineering, and carbon composites were also reviewed. [24,42,43] In addition, some reviews reported the advances and optimization strategies of the carbons and carbon-incorporated anodes for SIBs and PIBs, respectively. [24,44] Our group has paid attention to the strategies to enhance the initial Coulombic efficiency of carbon anodes for SIBs, [32] which was also attracted attention by He et al and Li et al [45,46] Except the material design, the reviews about the electrolyte design strategies, [47][48][49][50][51] and interfacial chemistries on carbon anodes for SIBs or PIBs were also studied, [49,50,52,53] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although various anodes (such as carbon materials, alloying materials, organic materials and metal chalcogenides) for PIBs have been reported, their applications in high power density PIBs still face challenges. [19][20][21][22][23][24][25][26][27][28] Among these materials, metallic Bi shows huge potential for high power density PIBs due to the suitable redox potential, high electronic conductivity, and large theoretical capacity. [29][30][31][32] However, Bi anodes generally suffer from large volume changes during the charge/discharge process and thus exhibit poor cycling stability.…”
Section: Introductionmentioning
confidence: 99%